2012
DOI: 10.1111/j.1464-5491.2011.03457.x
|View full text |Cite
|
Sign up to set email alerts
|

Automated identification of miscoded and misclassified cases of diabetes from computer records

Abstract: Aims To develop a computer processable algorithm, capable of running automated searches of routine data that flag miscoded and misclassified cases of diabetes for subsequent clinical review. Method Anonymized computer data from the Quality Improvement in Chronic Kidney Disease (QICKD) trial (n = 942 031) were analysed using a binary method to assess the accuracy of data on diabetes diagnosis. Diagnostic codes were processed and stratified into: definite, probable and possible diagnosis of Type 1 or Type 2 diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…This study confirms the findings of previous research which identified different types of errors and discrepancies in the recording of information about diabetes 57,16,18,19. Practitioners using CMR will increasingly need access to tools, which identify and allow for correction of diabetes related coding errors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study confirms the findings of previous research which identified different types of errors and discrepancies in the recording of information about diabetes 57,16,18,19. Practitioners using CMR will increasingly need access to tools, which identify and allow for correction of diabetes related coding errors.…”
Section: Discussionsupporting
confidence: 89%
“…For example, a person who really has T2DM is classified as T1DM 7. This matters because management plans, treatment goals and educational programmes are orientated towards the correct type of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…With further research, automation of these processes might be possible, which would allow searches to be even more user friendly. Algorithms that can be processed by machines appear to achieve similar results 16. There is also the need to consider similar toolkits for patients at risk of developing diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The primary dataset for the present retrospective cohort study was derived from individuals aged 18–90 years with a new diagnosis of T2D between January 1990 and April 2007, who had been registered with the general practice for at least 12 months. Rigorous classification techniques were used to ensure correct identification of patients with T2D (which used algorithms based on age at diagnosis, type of treatment, and age at treatment), with exclusion of patients with gestational diabetes, drug‐induced diabetes, and minimizing the risk of including patients with type 1 diabetes …”
Section: Methodsmentioning
confidence: 99%